The post-dictatorship memory politics in Portugal which erased political violence from the collective memory - Silva, R. Da; Ferreira, A. S. (Integrative Psychological and Behavioral Science, 2018)
Former clandestine militants’ voices and stories have been recurrently silenced in the Portuguese “battle over memory”, because their activities were linked to events, such as the Revolution of 25 April 1974, which have themselves been politically and socially depreciated in mainstream political narratives. Only recently did the traditional political narratives start to be questioned and debated by Portuguese scholars. Such political narratives took root in the country in the decades that followed the April Revolution, with various scholars and politicians denying the fascist categorisation of Estado Novo and adopting an authoritarian, non-totalitarian and non-fascist perspective, while recurrently depicting the Revolution as highly negative (namely as the source of the economic troubles of the country). Thus, for a long time, Portuguese conservatives opted to avoid debates on the 48 years of the Estado Novo’s regime which, among other things, maintained a very repressive and violent political police force, a camp of forced labour in Cape Vert known as Tarrafal, and a Colonial War on three African fronts. This article examines the existent academic publications which counter such oblivion of memory regarding armed struggle in Portugal. It also explores the reasons behind, on the one hand, the whitewashing of Estado Novo and the historical revisionism typical of the 1970s and 1980s, and, on the other hand, the “rebellion of memory” which emerged in the 1990s.